Memfasilitasi Peserta Didik untuk Mengembangkan Potensi Non Akademik - Dorlan Naibaho; Tiomia Clodianti Tampubolon (Jurnal Mahasiswa Kreatif, 2024)
Education plays an important role in improving the quality of human resources. Through education, students are expected to acquire the right intelligence, skills, and attitudes towards life in order to successfully face their environment. However, there are still many parents and teachers who only prioritize their children's academic ability and prioritize grades. There are differing views on this issue as to whether parents and teachers prioritize student academic achievement or student non-academic achievement. Even if children are created differently for something bigger in this world. Yes, a student's achievement is not only achieved through academic achievement, but also through non-academic achievement, students can develop their potential according to their talents and become great in their own way. Intelligence or intelligence can be described as the ability to understand the world, think rationally, and use resources effectively when faced with difficulties. Intelligence or intelligence can be described as the ability to understand the world, think rationally, and use resources effectively when faced with difficulties. God created man with a wide variety of abilities, talents, and natural intelligence (IQ). In addition, basically every human being is born with a hidden set of intelligences waiting to be developed in order to improve his abilities and achieve his dreams and goals in life.